Interfacial micromechanics modelling with fractal theory - Harris Iskandar Bin Ismail (Nanyang Technological University, 2023)
To understand how fractal parameters affect the dynamic properties of real-life structures such as aircraft fuselages and building structures, an improved contact model of a joint interface is proposed, and it includes the transition region demarcating the elastic and the plastic region. Thereafter, detailed numerical analysis is conducted to obtain the revised contact load and the contact stiffnesses equations. The stiffnesses consists of the normal and the tangential contact stiffness. Relationships are then established to further understand the effect of applied contact load to the 2 aforementioned contact stiffnesses. Numerical simulation using MATLAB is then employed to analyse the corresponding effects of various parameters to the translational contact stiffness based on the applied load. Then, Finite Element Analysis (FEA) software, ABAQUS, is further conducted to explore how these various parameters affect the dynamic properties of the contact model in natural frequency measured in 6 different modes of shapes. The contact model in FEA is modelled as the hybrid model, in which the materials are the isotropic aluminium alloy 7075-T651 and the orthographic carbon/epoxy composite.